Payment reporting system (PRS) / Mohd Noorazli Nasikin - Nasikin, Mohd Noorazli (2007)
A computerized system help in reducing the work cycle and make the business process become more effective and efficient. With the existing of the internet, having a computerized system will give a competitive advantage to organization. A system with a proper interface will lead to effectiveness of using the system. So this research had been done to develop a proper payment reporting system with an effective user interface that will replace current paper based system at Pejabat Pengurusan Fasiliti(PPF) at Universiti Teknologi MARA. To ensure the successfulness of the research, software development life cycle (SDLC) methodology is used as the guideline and the system design of this system was design by using the object oriented concept. Meanwhile to design the effective user interface, direct manipulation interface concept had been applied into the system interfaces. Interviews had been done and materials had been collect to analyze the system requirement. After analyzing and designing, a payment reporting system with effective user interface had been developed. By implementing direct manipulation concept into the interfaces, effective user interfaces had been design and develop, and a proper system had been developed to report payment. To make this system a better system, it is recommended to enhance and improve the functionality of the system and attractiveness of the interfaces.